2016
DOI: 10.1111/dme.13092
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing diabetes control in people with Type 2 diabetes through nurse‐led telecoaching

Abstract: Nurse-led telecoaching improved glycaemic control, total cholesterol levels and BMI in people with Type 2 diabetes. Twelve months after the intervention completion, there were sustained improvements in glycaemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(121 citation statements)
references
References 28 publications
3
118
0
Order By: Relevance
“…The evidence to support telecoaching in cardiac rehabilitation has been growing [32, 33] and may offer a solution for some patient groups. Of all the telecoaching programmes in chronic conditions, the COACH Program merits special attention, as in the past 15 years it has proved effective in different chronic conditions, including diabetes and coronary heart disease, and in diverse cultural contexts [12, 13, 34]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence to support telecoaching in cardiac rehabilitation has been growing [32, 33] and may offer a solution for some patient groups. Of all the telecoaching programmes in chronic conditions, the COACH Program merits special attention, as in the past 15 years it has proved effective in different chronic conditions, including diabetes and coronary heart disease, and in diverse cultural contexts [12, 13, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Two hundred and eighty-seven patients with type 2 diabetes were randomised to the intervention group and received the COACH Program (TCP), delivered by certified diabetes nurse educators after additional training [13]. The intervention consisted of 5 monthly telephone sessions of 30 min on average and was focused on achieving guideline-recommended diabetes treatment targets through regular control of diabetes risk factors including self-monitoring of blood glucose, appropriate lifestyle adjustments and intensification of medication therapy upon a patient consultation with GP [12]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the motivation of the professional, it is also evident how there are variations in the results of the patients by groups according to the professional who provides the education. In some studies, the professionals underwent a period of training before starting the diabetes education (Jutterström et al, ; Khunti et al, ; Mash et al, ; Odnoletkova et al, ). The importance of specialization in health personnel to carry out diabetes education is therefore highlighted in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Each study reported detailed information about the intervention time and intervention procedures. In the included studies, the intervention group procedure included automated telephone calls and nurse telephone follow-up (Piette et al, 2001(Piette et al, , 2000, nurse telephone follow-up (Aliha et al, 2013;Aytekin et al, 2016;Borhani et al, 2013;Crowley et al, 2013;Elgaphar, 2017;Kotsani et al, 2018;Nesari et al, 2010;Wong, 2005;Solaiman, 2016), multifaceted nurse-coaching intervention (Navicharern et al, 2009), short message service (Zolfaghari et al, 2012), nurse-led telephone coaching (Blackberry et al, 2013;Odnoletkova et al, 2016;Young et al, 2014), monthly video conferences with a nurse-coaching intervention (Hansen et al, 2017), and synchronous or asynchronous communication and webbased intervention (Bond et al, 2007) (Table 2). The results showed that the intervention period ranged from 3 to 18 months.…”
Section: Intervention Characteristicsmentioning
confidence: 99%